Inattention and the taxation bias - Jérémy Boccanfuso; Antoine Ferey (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper shows that agent inattention to taxes generates a time-inconsistency problem in the choice of tax policy. In equilibrium, inattention leads to inefficiently high tax rates and a taxation bias emerges. Combining structural and sufficient statistics approaches, we quantify the magnitude and the welfare effects of this policy distortion for US income tax rates, and find that the taxation bias is large, alters the progressivity of income taxes, and significantly reduces social welfare. Overall, our findings shed new light on the policy and welfare implications of inattention and misperceptions.
Keywords: H21; D03; 330; Optimal taxation; inattention